THE DEVELOPMENT OF CHRONIC NON-CALCULOUS CHOLECYSTITIS ON A BACKGROUND OF METABOLIC SYNDROME IN VIEW OF THE FUNCTIONAL STATE OF THE LIVER - Вірстюк, Н. Г.; Сенютович, Н. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the relevance of chronic non-calculous cholecystitis СNС and modern aspects of its development in view of the metabolic syndrome and of the functional state of the liver. The problem of chronic non-calculous cholecystitis (СNС) is important in connection with spread of disease, tendency to relapse and chronization of pathologic process, leading to prolonged disability. СNС often combined with other somatic disorders, including obesity, which carries comorbid character as so as in the basis of their pathogenic mechanisms are a metabolic disorders. Based on the analysis literary sources described impact on the development СNС blood lipid spectrum, biliary dyskinesia, activation of lipid peroxidation, the overproduction of cytokines such as IL-6, IL-8, IL-β, TNF-α, leptin, stimulating the metabolism of connective tissue – the proliferation of fibroblasts, collagen synthesis, activating the process of rebuilding connective tissue. Prospects for further research are specified.